2019
DOI: 10.1038/s41419-019-1877-6
|View full text |Cite
|
Sign up to set email alerts
|

Lactate and pyruvate promote oxidative stress resistance through hormetic ROS signaling

Abstract: L-lactate was long considered a glycolytic by-product but is now being recognized as a signaling molecule involved in cell survival. In this manuscript, we report the role of L-lactate in stress resistance and cell survival mechanisms using neuroblastoma cells (SH-SY5Y) as well as the C. elegans model. We observed that L-lactate promotes cellular defense mechanisms, including Unfolded Protein Response (UPR) and activation of nuclear factor erythroid 2–related factor 2 (NRF2), by promoting a mild Reactive Oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(110 citation statements)
references
References 65 publications
5
104
0
1
Order By: Relevance
“…GO enrichment analyses were conducted for DEGs in all the contrasts. Female responses to oxidative stress at 3 h demonstrated up-regulation of hydrolytic activity and peptidolytic activity dealing with damaged cellular components, but these activities seemed to cease at 6 h. Additionally, pyruvate and lactate transport were active across the two time points in females, protecting cells from oxidative stress by activating cellular defense and antioxidant actions [ 63 , 64 ]. Some effects on neural system were also observed at 6 h in both sexes, suggested by the up-regulation of synaptic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…GO enrichment analyses were conducted for DEGs in all the contrasts. Female responses to oxidative stress at 3 h demonstrated up-regulation of hydrolytic activity and peptidolytic activity dealing with damaged cellular components, but these activities seemed to cease at 6 h. Additionally, pyruvate and lactate transport were active across the two time points in females, protecting cells from oxidative stress by activating cellular defense and antioxidant actions [ 63 , 64 ]. Some effects on neural system were also observed at 6 h in both sexes, suggested by the up-regulation of synaptic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms mentioned above are likely brought on by low blood pressure and a hypercoagulation state by the direct and indirect action of SARS-Cov-2. Also, acidosis, high lactate, or hyperbilirubinemia have also been observed in most patients, which are all features related with oxidative stress mechanisms [ 102 , 103 ] and antioxidant responses [ 104 ]. Severe COVID-19 patients with developed typical clinical manifestations of septic shock, such as serum lactate levels >2 mmoL L −1 and persistent hypotension despite fluid resuscitation, generally require vasopressors to maintain MAP ≥ 65 mm Hg [ 105 ].…”
Section: Critically Ill Covid-19 Patients Show Clinical Manifestatmentioning
confidence: 99%
“…Therefore, we hypothesize that ROS are also the determinant of this metabolic alteration. Furthermore, as reported by Tauffenberger et al, lactate may promote oxidative stress resistance through ROS signaling, as seen in neuroblastoma and in the nematode Caenorhabditis elegans [26]. High content of lactate and choline, and low levels of citrate, glutamine, and glutamate were reported by Ryoo et al [27] in malignant thyroid nodules, and were suggested as the discriminative markers for determining the preoperative metabolomic profile of thyroid nodules.…”
Section: Discussionmentioning
confidence: 78%